Landscape features outside the airport exerted direct and indirect impact on bird community characteristics inside the airport - Xunqiang Mo; Jianzhong Xu; Mengxuan He; Ziyi Wang; Hong Yuan; Yuyue Wang; Ranran Wu; Linghui Tian; Weiying Chen; Lanlan Li (Global Ecology and Conservation, 2025)
The presence of bird communities within an airport can impact the likelihood of bird strikes occurring, with airport birds often being influenced by the surrounding habitat. When implementing measures to prevent bird strikes, one effective approach involves modifying the landscape around the airport to alter the birds within the airport. However, the relationship between landscape features and bird characteristics inside the airport remains unclear, posing challenges for bird strike management. In our study, we examined landscape features surrounding the airport and bird community characteristics both inside and outside the airport over three years. Our research aimed to investigate how the landscape features influenced external bird characteristics and subsequently impacts the bird community within the airport. The results revealed that: (1) Passeriformes were the dominant birds detected inside the airport, with Passer montanus being the most abundant species, followed by Alauda arvensis and Hirundo rustica. (2) Airport displayed a complex bird network, with Passeriformes playing significant roles in connecting woodland, abandoned area, and park. Furthermore, bird community composition of the airport differed significantly from those in woodland, abandoned area, and park. (3) Landscape features directly influenced bird community network characteristics within the airport, as well as impacting bird community diversity. In abandoned area, landscape features affected bird community diversity outside the airport, subsequently influencing the network and diversity characteristics of bird community within the airport.